2019
DOI: 10.1016/j.jelekin.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical loading and muscle activation of four common exercises used in osteoporosis prevention for early postmenopausal women

Abstract: High impact exercise can reduce postmenopausal bone loss, however stimulus frequency (loading cycles per second) can affect osteogenesis. We aimed to examine the effect of stimulus frequency on the mechanical loading of four common osteoporosis prevention exercises, measuring body acceleration 2 and muscle activation with accelerometry and electromyography (EMG), respectively. Fourteen early postmenopausal women completed randomised countermovement jumps (CMJ), boxdrops (BD), heel-drops (HD) and stamp (STP) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…Osteoporosis (OP) is a progressive bone disease characterized by low bone mass and degeneration of bone microstructure, which leads to increased bone brittleness and an increased risk of fracture [ 76 ]. Many studies have shown that proper exercise or mechanical stimulation can prevent or treat OP [ 97 , 98 , 99 ].…”
Section: Piezo Channels and Bone Diseasementioning
confidence: 99%
“…Osteoporosis (OP) is a progressive bone disease characterized by low bone mass and degeneration of bone microstructure, which leads to increased bone brittleness and an increased risk of fracture [ 76 ]. Many studies have shown that proper exercise or mechanical stimulation can prevent or treat OP [ 97 , 98 , 99 ].…”
Section: Piezo Channels and Bone Diseasementioning
confidence: 99%
“…When the Soviet astronauts flew in space for 75 to 184 days, the bone mineral density (BMD) of the calcaneus decreased 0.9–19.8%, and the spine BMD decreased about 0.3–10.8% for the astronauts who stayed at the Salute Space Station for 5 to 7 months 4 . At present, several preventative and therapeutic strategies have shown good efficacy for bone loss induced by spaceflight, such as physical exercise, mechanical stimulation and drug therapy 5 , 6 , but still have certain limitations and significant deficiencies. Among them, drug treatments such as bisphosphonates have significant protective effects on bone loss induced by microgravity, but there were the inevitable side effects, such as osteonecrosis of the jaw, headache and nausea 7 – 9 .…”
Section: Introductionmentioning
confidence: 99%
“…6 Notably, high-impact exercise can reduce postmenopausal bone loss. 7 In addition, dyslipidemia is one of the lifestyle-related diseases that often occur in women after menopause. 8 It is known that estrogen deficiency associated with menopause affects lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, male hormones are the only source of female hormones after menopause. Therefore, correlation (7) holds: male hormone ! female hormone…”
Section: Introducing Deviationmentioning
confidence: 99%